Pengenalan linguistik - Nazir, Faridah; Rosly, Nurul Jamilah; Saimon, Aminnudin; Senawi, Balqis (MK e-Solutions Sdn. Bhd, 2025)
Linguistics is a study of language, so the introduction to this knowledge is very important. Knowledge of linguistics is related to the characteristics of language studies, the nature of language, reflections on the thoughts of linguistic figures and the history of the development of linguistics; external factors or paralinguistics, language variations, paradigmatic rules, stylistics and scientific language. In this regard, this book Introduction to Malay Linguistics describes in detail the field of linguistics and the nature of language; the history of the development of linguistics; linguistic structure, external factors, language variations, and paradigmatic rules; stylistic elements in prose and poetry; and the characteristics of the scientific Malay language. This book provides students with a general overview of the basics of language and linguistics, focusing on the nature of language, the basic concepts of the sound system (phonology), word formation and structure (morphology), sentence structure (syntax), the meaning of words and expressions (semantics). It will also discuss child language acquisition, dialects, social aspects of language and language change. This book contains 14 chapters to help students understand linguistic concepts with the help of various illustrations in the form of diagrams and related tables.